The Description of Knowledge about Antenatal Care in Village X Bandung Regency in 2019 - Antri Ariani; Andria Pragholapati (Journal of Ners and Midwifery, 2021)
The lack of maternal Antenatal care visit is one of the determinants that cause maternal mortality rates in Indonesia. Antenatal care is care for pregnant women during pregnancy, starting from conception to the birth of the fetus. The purpose of this study was to study the Antenatal Care Knowledge Overview in Village X Bandung Regency in 2019. The design of this study was quantitative descriptive with 74 postpartum mothers respondents. Data were collected using a knowledge questionnaire. The results obtained from the knowledge of Antenatal Care in Village X Bandung Regency in 2019 were high knowledge of Antenatal Care (73%) and low knowledge of 27%. The conclusion of the study showed respondents who had high knowledge of ANC was more than 73% compared to those who had low knowledge of 27%. Health workers need to improve health education for mothers with high gestational age and home visits.